SIMULASI DESAIN SKEMA ROBOT LINE FOLLOWER PENYIRAM TANAMAN MENGGUNAKAN SIMULATOR SOFTWARE PROTEUS 8: Rini Nuraini - Jurnal, Redaksi Tim (PETIR, 2018)
The problem of high wages of labor today is very consideration to do things that routine work done every day, as well as watering plants, for this case, need a solution to the problem, that is by making a robot to do it. Robot Line Follower Sprinkler Plants or the next one will be shortened to LFPT Robot, the goal to do the work routinely watering the plant by way of the robot is running while watering the plants on the track. The LFPT Robot Characteristics of the robot will run following a specified black line, with the help of two IR sensors on the front of the robot for running, as well as an IR sensor on the left and right side of the LFPT Robot to detect the presence of plants. If the sensor on the left and right side of the robot detects a black line, the LFPT Robot will stop and will direct the water hose to the left and right then the robot will do the watering. This study uses a series of IR sensors to detect black lines. The LFPT Robot works will follow a black line, and will stop when the sensors on the left and right sides of the robot detect a black line. The results obtained a design of an LFPT Robot, which can be simulated directly by using Proteus 8 Software Simulator.